The development of a courseware on Malaysian endangered wildlife using multiple intelligence theory / Nur Farhana Azman - Azman, Nur Farhana (2019)
The focus of the project on developing multimedia courseware for Malaysian educational about the endangered wildlife in Malaysia. The Development of a Courseware on Malaysian Endangered Wildlife Using Multiple Intelligence Theory was developed based on a PERHILITAN. The scope for the courseware of the endangered wildlife in Malaysia focused on Malaysian age between 16 years old and above. The development of a courseware on Malaysian endangered wildlife using ADDIE model. The phases of the project framework consist of initial study, analysis, design, development, evaluation, and reporting. The development of a courseware on Malaysian endangered wildlife using multiple intelligence theory based on visual intelligence, intrapersonal intelligence, logical/mathematical intelligence, and natural intelligence. The delivery of content method using CD based. The courseware will be delivered in CD based and give it to the user. The functionality and usability of the courseware evaluated and tested for the Malaysian age between 16 years old and above.